2016
DOI: 10.1007/s40261-016-0477-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dexmedetomidine as an Adjuvant in Epidural Analgesia and Anesthesia: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: This systematic review and meta-analysis demonstrates that dexmedetomidine as an adjuvant in epidural procedures is generally safe and well tolerated. Furthermore, dexmedetomidine acted synergistically and provided an improved sedation and analgesic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 55 publications
4
49
0
Order By: Relevance
“…neurons, hyperpolarizing the neuron membrane potentials via G-protein-mediated activation of K + , decreasing sympathetic outflow and norepinephrine release, thus inhibiting the transmission of nociceptive information (7,30). Therefore, the combination of these drugs theoretically produces a synergistic analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neurons, hyperpolarizing the neuron membrane potentials via G-protein-mediated activation of K + , decreasing sympathetic outflow and norepinephrine release, thus inhibiting the transmission of nociceptive information (7,30). Therefore, the combination of these drugs theoretically produces a synergistic analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The two agents mediate their analgesic effect by stimulating the α2 receptor located post-synaptically on the dorsal horn of the spinal cord (6). A recent systematic meta-analysis demonstrated that dexmedetomidine as an adjuvant in epidural anesthesia provided improved sedation and analgesia with a well-documented safety profile (7). Several studies involving epidural dexmedetomidine in obstetric populations have been published: Dexmedetomidine added to combined spinal (bupivacaine)-epidural (fentanyl) anesthesia for cesarean section (1,2); combined epidural dexmedetomidine and ropivacaine for post-cesarean analgesia (8); and epidural dexmedetomidine combined with ropivacaine or bupivacaine for labor analgesia (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Dexmedetomidine has also successfully been used in central neuraxial block along with local anesthetic agents. [ 25 26 ] Again while performing peripheral nerve block or nerve plexus block, dexmedetomidine has shown its perfect adjuvant role in all the cases. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…The pro-analgesia effect is achieved via peripheral action [ 31 ], but the promotion of sedation may be due to a systemic mechanism. The sedation resulting from paravertebral DEX may be caused by increased plasma concentrations through local absorption [ 32 ]. The advantage of paravertebral DEX administration is that sedation could develop both through peripheral and systemic mechanisms.…”
Section: Discussionmentioning
confidence: 99%